STRATEGI PEMBERDAYAAN PNS DALAM RANGKA REFORMASI BIROKRASI - Ashari, M.Si, Dr. Edy Topo (Pusjar SKPP Lembaga Administrasi Negara, 2010)
Human resource is especial asset in an organization and it as one of most important element and also very determining in efficacy of organization to reach the target. So also in government sector, human resource ( civil servant / PNS) take hold of important part to well-held an efficient and effective government. Thereby, the effort to make-up the quality of civil servant is very important to be conducted in a continuously in order to governmental duty as society servant can better ambulatory. The effort that can be conducted to increase quality of civil servant is “the empowerment